Malignant mixed mesodermal tumors of the uterus. - Alleyn, James (2015)
We have seen over the past six years, a gradual increase in the number of mixed mesodermal tumors of the uterus. In this study he was diagnosed, treated and followed a total of 41 patients in an institution and by the same doctors. the stories were reviewed with particular attention to clinical factors such as previous radiation, estrogen use, race, laboratory, etc. The sheets were studied and myometrial tumor penetration was determined. In twelve patients, the initial diagnosis was wrong, and r revised tissue sent to our institution revealed the existence of sarcoma and carcinoma. This factor can influence the increased incidence of this rare tumor. Patients were initially treated with surgery alone, and in later stages of this study was combined surgery and radiation. Survival at 3 years was 15%. No significant difference in survival between those who had surgery alone and those in which external radiation was added was found. Yes myometrial significant correlation between penetration and survival was found. In most patients myometrial deep penetration of the tumor was found. Serum levels of LDH were elevated in 72% of patients. high elevations was found when the disease was advanced.